Economic Education as a Foundation for Macroeconomic Stability: Unveiling the Mediating Role of Financial Literacy - Andri Octaviani; Waspodo Tjipto Subroto; Norida Canda Sakti (International Journal of Multidisciplinary Approach Research and Science, 2026)
Macroeconomic stability is a vital foundation for sustained economic growth; however, the mechanisms by which economic education influences aggregate stability have not been fully mapped. This study aims to examine the influence of economic education on macroeconomic stability, with financial literacy as a mediating variable and digital financial inclusion as a moderating variable. Employing a quantitative explanatory approach, data were collected from 400 respondents of productive age in Indonesia through structured online surveys (September-November 2025). Data analysis utilised Partial Least Squares - Structural Equation Modelling with SmartPLS 4.0. Results demonstrate that economic education positively and significantly influences macroeconomic stability (β=0.215, p=0.001). Financial literacy was partially confirmed to mediate this relationship (β=0.340, p<0.001), functioning as a crucial transmission mechanism through risk management, savings, and policy channels. Furthermore, digital financial inclusion was found to moderate positively (β=0.185, p=0.004), strengthening the impact of financial literacy on economic stability; higher digital access accelerates the effectiveness of prudent financial decision-making. These findings extend Human Capital Theory by demonstrating that the impact of economic education transcends individual productivity to encompass the resilience of the national economic system. Practically, the research recommends integrating financial life-skills curricula and digital inclusion policies accompanied by educational verification to mitigate systemic risks, particularly in emerging markets such as Indonesia.